Ideological Anxiety, National Transition and the Uncanny in The Omega Factor. Issue 1 (January 2016) - Cramer, Steve
Abstract : This article examines the BBC Scotland series The Omega Factor (1979), with a view to illustrating the ways in which the series used its supernatural genre to interrogate the ideological transitions of its era. In particular, the article will examine the ways in which Scotland's cultural landscape and history is misrecognised through the eyes of characters from the metropolitan English centre, who journey into a Kristevan uncanny in their experience of otherness in Scottish characters and landscapes. The ways in which The Omega Factor diverged from generic precedents set by contemporary English supernatural series of the time will also be illustrated, particularly with regard to ideological subtext and notions of decentred history.